Sourcing and framing in cancer control continuum: A content analysis of Malaysian English and Chinese online cancer news - Zhang, Thomas Hongjie; Tham, Jen Sern; Yu, Xueyong; Chang, Peng Kee; Kho, Suet Nie (Frontiers in Public Health, 2022)
Background In health news production, sourcing and framing are two critical mechanisms that influence how newsreaders think about and perceive the severity of a health issue. Understanding how local media covers the cancer control continuum is vital. However, very limited studies have looked at the effect of sourcing and framing in cancer news coverage, and it is still unknown how sources and news frames shape cancer coverage, especially in non-Western countries. Objective This study examines framing and sourcing patterns in news stories reporting on cancer control in Malaysian mainstream (English) and ethnicity (Chinese) online news sites, uncovering underlining associations between essential news components, source, and framing. Methods We used a predesigned code book to conduct a quantitative content analysis on cancer news stories (n = 841) published on two Malaysian English and Chinese online news sites from 2017 to 2019. Cancer news received adequate coverage in Malaysian English and Chinese media and was also session-centered. Results Two logistic regression models demonstrated the internal relationships between sourcing, framing, and different elements in cancer coverage. In terms of news sources, the results revealed that medical journals were the most likely to be cited when the news focused on medical research, followed by primary cancer prevention. When the news concentrated on statistical cancer reports and environmental/occupational risk factors, government agencies were more likely to be interviewed. Of news frames, when the news articles engaged with medical institutions and mentioned medical publications, the lifestyle frame was very likely to be shown, but the environmental frame was more likely to be portrayed when interviewing medical practitioners. Conclusion This study is the first comprehensive assessment to analyze and compare Malaysian English and Chinese online cancer news coverages and uncover underlying associations between news components, sourcing, and framing paradigms. We contributed to the scholarly understanding of cancer news coverage. This study can serve as a model for future health promotion researchers, journalists, and policymakers. Implications for cancer risk communication research, health journalist practices, and health policymaking were discussed.